The Relationship Between Metabolic Syndrome with Incidence of Stroke - Fila Fatmisua Chrisna; Santi Martini (Universitas Airlangga, 2016)
Stroke is one of non-communicable diseases and affected by many risk factors. Some stroke risk factors have in common with the metabolic syndrome criteria, such as abdominal obesity, glucose intolerance, decreased HDL cholesterol, elevated triglyceride levels, and insulin resistance. The goals to analyze the relationship between the metabolic syndrome with the incidence of stroke. This research is analytic by using case-control design. The case groups were hospitalized patients of stroke and undergoing inpatient in dr. M. Soewandhie Surabaya. The case groups were 32 peoples and control group 32 peoples were selected at random. The variables studied were age, sex, metabolic syndrome, the first criteria, the second criteria of metabolic syndrome, and the third criteria of metabolic syndrome. The results showed that the majority of stroke patients in the age range 51-75 years (78%). Results of Chi-Square test indicates a significant relationship between the metabolic syndrome criteria first (abdominal obesity, triglycerides, and HDL cholesterol levels) p = 0,01 OR = 6,82 (95% CI = 1,23 to 68,17 ) and the second criteria of metabolic syndrome (HDL cholesterol, blood pressure, and fasting glucose levels) p= 0,007 OR = 5,80 (95% CI = 1,30 to 35,15) with the incidence of stroke. While for the third criteria of metabolic syndrome (fasting glucose levels, abdominal obesity, triglyceride  levels) there was no significant relationship to the incidence of stroke. It is expected for people, especially over the age of 35 years can do a lipid profile and circle abdominal measurements to detect of   metabolic syndrome and the risk of stroke. Keywords: Metabolic Syndrome, Stroke, Abdominal Obesity, Triglyceride, HDL